Differences and mechanisms underpinning a change in the knee flexion moment while running in stability and neutral footwear among young females - Timothy A. Sayer; Rana S. Hinman; Kade L. Paterson; Kim L. Bennell; Karine Fortin; J. Kasza; Adam L. Bryant (Journal of Foot and Ankle Research, 2019)
Abstract Background Higher peak external knee flexion moments (KFM) during running has been observed in healthy people wearing athletic footwear compared to barefoot, which may increase risk of knee pathologies such as patellofemoral pain. Currently, no studies have examined whether stability and neutral style athletic shoes influence the peak KFM differently, or explored the underlying biomechanical mechanisms by which footwear alters peak KFM in young females. Methods Lower limb biomechanics of sixty girls aged between 10 and 25 years old were collected while running in footwear (both stability and neutral) and barefoot. The external peak KFM, sagittal plane kinematics, sagittal plane knee ground reaction force (GRF) lever arm and sagittal plane resultant GRF magnitude were analysed by repeated measures Analysis of Variance. Linear mixed models were fit to identify predictors of a change in peak KFM, and to determine if the effects of these predictors differed between footwear conditions. Results The peak KFM was higher wearing both shoe styles compared to barefoot (p < 0.001), while no between-shoe differences were found (p > 0.05). Both shoes also increased kinematic variables at the hip, knee, and ankle (p < 0.05). When all these variables were entered into the mixed model, only a change in the knee-GRF lever arm was predictive of a change in peak KFM wearing shoes compared to barefoot (p < 0.001). Conclusion These findings provide evidence that stability and neutral shoes increase peak KFM compared to barefoot, which is associated with a change in the knee-GRF lever arm rather than a change in lower limb kinematics. Future studies may consider manipulating footwear characteristics to reduce the knee-GRF lever arm in an effort to reduce peak KFM and the potential risk of patellofemoral pain.